ANALYSIS OF NURSE UNIT MANAGER SUPERVISION ON THE PERFORMANCE OF NURSES AT X HOSPITAL KEDIRI CITY, INDONESIA: A CROSS-SECTIONAL STUDY - Efendy, Mohamad As'ad; Prisantika, Emeylian Dhea (Journal of Public Health Research and Community Health Development, 2023)
Background: Hospital performance challenges are receiving attention because they concern the efficiency and effectiveness of human resources in accomplishing organizational objectives and visions. Many factors influence performance, including superiors' supervision, which has an impact on the organization's overall performance results. In fact, supervision has not been carried out optimally.  Purpose: to analyze how the nurse unit manager's supervision affected nurse performance. Methods: A correlational study methodology was used on 67 nurses from the inpatient room. To obtain 57 individuals, a stratified random sampling procedure was used. The data was analyzed using the Spearman rho statistical test, with a significance threshold of = 0.05. Results: From 67 respondents, 33 respondents (57.9 percent) stated that the nurse unit manager offered acceptable supervision. The 32 respondents (56.1 percent) had adequate performance. Result of the Spearman rho test obtained a p-value = 0.000 which is less than the value of alpha (0.05), so it can be concluded that H0 is rejected, meaning that there is a relationship between the supervision of the head of the room and the performance of nurses at X Hospital Kediri City. Conclusion: It was concluded that there is a link between the nurse unit manager's supervision and the performance of nurses. The study's findings also suggest that supervision can increase nurse performance because, when supervising the nurse unit manager evaluates certain activities directed at nurses, if the evaluation is corrected by the nurse, it can improve the nurse's performance.